Lived experiences of hypertensive older adults living alone in Kendari City: a phenomenological aprroach - Prio, Asminarsih Zainal; Sahar, junaiti; Rekawati, Etty (Jurnal Ners, 2024)
Introduction: This study aimed to explore lived experiences as evidence-based in developing health services for hypertensive older adults living alone. Methods: This study employed a qualitative phenomenological approach, with in-depth and semi-structured interviews of hypertensive older adults living alone in Kendari City Southeast Sulawesi. Purposive sampling was utilized. 15 participating older adults, predominantly female, and with ages ranging from 61-80.  Data were collected from April until July 2022, and Colaizzi’s steps were used to guide the data analysis. Results: Three themes were identified: 1) health changes in the older adults living alone consisting of physical, emotional, social, and spiritual changes; 2) coping mechanisms consisting of emotion-focused coping, biobehavior-focused coping, social-focused coping, and spiritual-focused coping; and 3) healthcare needs consisting of health information needs, regular health checks, group activities, and spiritual activities. Conclusions: This research highlights the needs of hypertensive older adults living alone to adapt to their health changes and requiring holistic hypertensive care as well as regular health services. Recommendations in this study include developing a holistic hypertensive care program consisting of physical, psychological, social, and spiritual activities. Further research needs to explore the effectiveness of holistic hypertension care on blood pressure, stress, coping, and quality of life of older adults with hypertension by comparing older adults living alone with older adults living with family, and qualitative research using ethnographic methods to determine the adaptation process of the older adults living alone according to culture.